Management of cN0 papillary thyroid microcarcinoma patients according to risk-scoring model for central lymph node metastasis and predictors of recurrence - Feng, J.-W.; Ye, J.; Wu, W.-X.; Qu, Z.; Qin, A.-C.; Jiang, Y. (Journal of endocrinological investigation, 2020)
Background The role of routine prophylactic central neck dissection (pCND) in clinically lymph node-negative (cN0) papillary thyroid microcarcinoma (PTMC) patients remains controversial. This retrospective study aimed to identify the clinical and pathologic factors of central lymph node metastasis (CLNM) and recurrence in PTMC patients. Methods A total of 371 cN0 PTMC patients from two hospitals were retrospectively analyzed. All patients underwent thyroidectomy plus pCND between January 2010 and January 2018. Clinicopathological features were collected, univariate and multivariate analyses were performed to determine the risk factors of CLNM. A scoring model was constructed on the basis of the results of independent risk factors of CLNM. The Cox proportional hazards model was used to analyze the risk factors of recurrence. Results CLNM occurred in 123 (33.2%) patients. Multivariate analysis showed male, tumor size > 0.75 cm, multifocality, extrathyroidal extension (ETE) and tumor in the middle/lower pole were independent risk predictors of CLNM ( P < 0.05). A seven-point risk-scoring model was established to predict the stratified CLNM in cN0 PTMC patients. Multivariate Cox regression model showed ETE, vascular invasion and CLNM were independent risk predictors of recurrence ( P < 0.05). Conclusion Our study suggested that routine pCND should be performed for cN0 PTMC patients with score ≥ 3 according to the risk-scoring model. Moreover, patients with risk factors of recurrence should consider more complete treatment and more frequent follow-up.